2016
DOI: 10.4236/jmf.2016.63030
|View full text |Cite
|
Sign up to set email alerts
|

On Steady Dividend Payment under Functional Mean Reversion Speed

Abstract: We study how firms' management can ensure steady dividend growth and payout to the shareholders in an emerging market. We create the dividend equalization reserve account whereby during high profit some amount of money is kept in order to top up dividends during deficiency. We use a mean reversion stochastic differential equation with a functional mean reversion speed to find the optimal dividend policy with optimal dividend equalization reserve. One of our results indicates that, it is optimal to pay high div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The econometricians and financial experts questioned the whole foundation of the efficient market hypothesis assumptions (Mtunya, Ngare, & Nkansah-Gyekye, 2016;Trypsteen, 2017). Thus, it is important to examine the alternative theories that can predict the market performance in an efficient manner.…”
Section: Substantiation From the Literaturementioning
confidence: 99%
“…The econometricians and financial experts questioned the whole foundation of the efficient market hypothesis assumptions (Mtunya, Ngare, & Nkansah-Gyekye, 2016;Trypsteen, 2017). Thus, it is important to examine the alternative theories that can predict the market performance in an efficient manner.…”
Section: Substantiation From the Literaturementioning
confidence: 99%
“…Further, after careful analysis the blame for drastic crises was put on the policies that were created by the financial system (e.g., İzgi, Duran 2016;Neaime 2015;Shaffer 2010;etc.). Making different econometricians, and financial practitioners from all around the world to question that is the foundation of the whole system based on a false assumption of efficient market hypothesis (e.g., Mtunya et al 2016;García et al 2015;Malkiel 2003;etc.). Thus, the growth of discontentment with this theory causes researchers to work on other theories that could help them to explain the market phenomenon.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, when prices fall back to their fundamental values, their return was only 4%. This showed that if their returns that are greater than the average then they will be followed by returns that are lower than the average (e.g., Mtunya et al 2016;Oikarinen, Schindler 2015;Engle, Morris 1991;etc. ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This developed in a family of Hamilton-Jacobi-Bellman variational inequalities whose solutions were approximated numerically. Mtunya A.P et al [29] showed how the firms financial management should safeguard a stable dividend payout growth for the shareholders as well as optimizing the dividend policy.…”
Section: Lin He and Zongxia Liangmentioning
confidence: 99%
“…c are given by(29).The general solution to the differential equation is given by are constants and ( ) p x and ( ) for the values of z, ( ) p x and ( ) q x in (32).…”
mentioning
confidence: 99%